Brief Report: The Unrealized Potential of Autonomous Vehicles for an Aging Population. Issue 5 (20th October 2019) - Pettigrew, Simone; Cronin, Sophie L.; Norman, Richard
ABSTRACT: Autonomous vehicles (AVs) have the potential to improve the health and well-being of older people. This exploratory study involved in-depth interviews with 43 key stakeholders across a broad range of sectors to identify the primary policy implications of AVs for aging populations. Four main issues were evident: a general lack of salience of the needs of older people in the AV discourse, the perceived dominance of the commercial drivers of AV technology, the implications of the particular characteristics of the senior segment, and a lack of available analyses to guide decision making. Threats and opportunities represented by these issues are discussed.